Pengaruh konsentrasi karagenan di dalam pembuatan nori daun binahong (Anredera cordifolia) - Karina Bianca Lewerissa; Sarlina Palimbong; Melinia Anggraini (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Nori is a sheet-shaped snack generally made from Porpyra red seaweed, which is not found in Indonesia. Meanwhile; the binahong plants (Anredera codifolia) are spread through out Indonesia. Binahong leaves are consumed without further processing. Binahong leaves are potential functional food, as they are rich in nutrient. They are high in vitamin A, and vitamin C. They also contain some protein, and fat. However, binahong leaves have bitter taste and unfavored flavor. In this study, binahong leaves were processed into nori with various concentrations of carrageenan. The concentrations of added carrageenan were 1, 2, and 3 %. The psychochemical properties of the resulting products were tested by proximate analysis and sensory tests. The result showed that the addition of carrageenan had no significant effect on water, protein, fat, and carbohydrate contents. However, it had significant difference on ash content. Sensory testing showed that there was no significant difference between treatments in terms of appearance, taste, aroma, texture, and overall assessment.